FePO4 NPs Are an Efficient Nutritional Source for Plants: Combination of Nano-Material Properties and Metabolic Responses to Nutritional Deficiencies - Sega, Davide; Baldan, Barbara; Zamboni, Anita; Varanini, Zeno (Frontiers in Plant Science, 2020)
Phosphorous and iron are a macro- and micronutrient, respectively, whose low bioavailability can negatively affect crop productivity. There is ample evidence that the use of conventional P and Fe fertilizers has several environmental and economical disadvantages, but even though great expectations surround nanotechnology and its applications in the field of plant nutrition, little is known about the mechanisms underlying the uptake and use of these sub-micron particles (nanoparticles, NPs) by crop species. This work shows that cucumber and maize plants both use the nutrients borne by FePO4 NPs more efficiently than those supplied as bulk. However, morpho-physiological parameters and nutrient content analyses reveal that while cucumber plants (a Strategy I species with regard to Fe acquisition) mainly use these NPs as a source of P, maize (a Strategy II species) uses them preferentially for Fe. TEM analyses of cucumber root specimens revealed no cell internalization of the NPs. On the other hand, electron-dense nanometric structures were evident in proximity of the root epidermal cell walls of the NP-treated plants, which after ESEM/EDAX analyses can be reasonably identified as iron-oxyhydroxide. It appears that the nutritional interaction between roots and NPs is strongly influenced by species-specific metabolic responses.